Effect of 2% Lignocaine Solution in Pain During Removal of Nasal Pack - Dhakal, Ashish; Shrestha, Bikash Lal; Pokharel, Monika (Journal of College of Medical Sciences-Nepal, 2019)
Background: Nasal packing is commonly done after septal surgeries. Nonabsorbable nasal pack is used to minimize bleeding from surgery site, support the mucoperichondrial flaps, and minimize the risk of formation of septal hematomas and adhesions. However, these materials cause pain and discomfort in-situ as well as during removal. This study was done to evaluate the effect of 2% lignocaine rehydration of nasal pack on pain during pack removal. Methods: This prospective study was conducted on 60 patients who had undergone septoplasty. The patients were divided into 2 groups: Lignocaine and Normal saline group, with 30 patients each. In the Lignocaine group, 2.5 ml of 2% of lignocaine was diluted with 2.5 ml of distilled water and was injected into the nasal pack; and in Normal saline group, 5 ml of normal saline was injected into the nasal pack. Nothing was injected to the left nostril, which acted as a control, in both groups. All patients were asked severity of pain during removal of nasal packing by VAS. Results: In lignocaine group, mean pain score was 3.73 ± 1.63 on lignocaine side and 6.23 ± 1.69 on control side (U=109.5, p<0.001). In Normal saline group, it was 6.5 ± 1.7 on normal saline side and 6.23 ± 1.96 on control side (U=425.5, p=0.711). On comparing VAS between lignocaine and normal saline group, pain was significantly lower in the lignocaine group (U=112.5, p<0.001) Conclusion: Rehydrating nasal pack with 2% topical lignocaine is a useful method to reduce pain during nasal pack removal.